2022
DOI: 10.1177/08862605221086642
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Contexts for Violence Against Women: Using Latent Class Analysis to Understand Structural and Contextual Drivers of Intimate Partner Violence at the National Level

Abstract: Introduction: Intimate partner violence (IPV) affects 1 in 3 women and poses a major human rights threat and public health burden, yet there is great variation in risk globally. Whilst individual risk factors are well-studied, less research has focussed on the structural and contextual drivers of IPV and how these co-occur to create contexts of high risk. Methods: We compiled IPV drivers from freely-accessible global country-level data sources and combined gender inequality, natural disasters, conflict, coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“… 6 , 11 , 12 More recent global evidence points towards intersecting structural factors, including conflict, colonialism, patriarchy, and climate change, in creating high risk contexts for IPV perpetration and experience. 13 …”
Section: Introductionmentioning
confidence: 99%
“… 6 , 11 , 12 More recent global evidence points towards intersecting structural factors, including conflict, colonialism, patriarchy, and climate change, in creating high risk contexts for IPV perpetration and experience. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Another factor consistently associated with IPV and suicide risk is having significant health problems [ 1 , 54 , 55 ]. In this study, around a third of the women reported having significant health problems, with no differences observed between IPVp and IPVp+ or between women with or without SI.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is a skew towards focusing on transforming gendered social norms and attitudes for adolescent IPV prevention, when norms and attitudes are only one of many drivers of IPV [1,85,86]. We only identified one intervention that had a central focus on an important and broadly recognised protective factor for IPV: education [1,87].…”
Section: Discussionmentioning
confidence: 99%